Joint Use of Skull Base Surgery in a Case of Pediatric Parotid Gland Carcinoma - Yuri Ueda; Kiyoaki Tsukahara; Kazuhiro Nakamura; Ray Motohashi; Minoru Endo; Hiroki Sato; Yasuaki Katsube; Mamoru Suzuki (Case Reports in Otolaryngology)
Parotid gland carcinoma is extremely rare in children. We report a case of pediatric parotid gland carcinoma with extensive infiltration into surrounding tissues including the skin and temporomandibular joint capsule at initial examination. Total resection of the parotid gland was conducted together with skull base surgery and mandibular dissection. The patient was a 14-year-old girl. In addition to the skin and temporomandibular joint, infiltration into the anterior wall of the external auditory meatus and masseter muscle was also seen, and T4N0M0 stage IV parotid carcinoma was diagnosed. Skin was resected together with the pinna, and temporal craniotomy and skull base surgery were performed to resect the temporomandibular joint capsule and external auditory meatus en bloc, and mandible dissection was conducted. Facial nerves were resected at the same time. Level I to level IV neck dissection was also conducted. A latissimus dorsi myocutaneous flap was used for reconstruction. The postoperative permanent pathology diagnosis was high-grade mucoepidermoid carcinoma with a low-grade component. Postoperatively, radiotherapy at 50 Gy alone has been conducted, with no recurrence or metastasis observed for over 4 years.